ppGpp-Dependent Negative Control of DNA Replication of Shiga Toxin-Converting Bacteriophages in Escherichia coli - Nowicki, Dariusz (American Society for Microbiology, 2013)
The pathogenicity of enterohemorrhagic Escherichia coli (EHEC) strains depends on the production of Shiga toxins that are encoded on lambdoid prophages. Effective production of these toxins requires prophage induction and subsequent phage replication. Previous reports indicated that lytic development of Shiga toxin-converting bacteriophages is inhibited in amino acid-starved bacteria. However, those studies demonstrated that inhibition of both phage-derived plasmid replication and production of progeny virions occurred during the stringent as well as the relaxed response to amino acid starvation, i.e., in the presence as well as the absence of high levels of ppGpp, an alarmone of the stringent response. Therefore, we asked whether ppGpp influences DNA replication and lytic development of Shiga toxin-converting bacteriophages. Lytic development of 5 such bacteriophages was tested in an E. coli wild-type strain and an isogenic mutant that does not produce ppGpp (ppGpp(0)). In the absence of ppGpp, production of progeny phages was significantly (in the range of an order of magnitude) more efficient than in wild-type cells. Such effects were observed in infected bacteria as well as after prophage induction. All tested bacteriophages formed considerably larger plaques on lawns formed by ppGpp(0) bacteria than on those formed by wild-type E. coli. The efficiency of synthesis of phage DNA and relative amount of lambdoid plasmid DNA were increased in cells devoid of ppGpp relative to bacteria containing a basal level of this nucleotide. We conclude that ppGpp negatively influences the lytic development of Shiga toxin-converting bacteriophages and that phage DNA replication efficiency is limited by the stringent control alarmone.